Ljubiteljsko gledališče kot način preživljanja prostega časa - Vrtovec Beno, Ana (Etnolog. Nova vrsta (Ljubljana), 2020)
In this article, the author presents a particular way of spending free time: joining an amateur drama group. On the basis of field work carried out among different amateur drama groups around Slovenia, the following are discussed: why individuals decide to spend their free time on this activity; what they expect to gain from taking part in it; and what this participation means and makes possible.
Keywords: amatersko gledališče; prosti čas; Slovenci